Pengaruh Sonikasi Terhadap Sifat Fisik Formula Herbisida yang Ditambahkan Surfaktan Dietanolamida - Ika Agustin Rusdiana; Erliza Hambali; Mulyorini Rahayuningsih (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2018)
Diethanolamide is a non-ionic surfactant from palm oil derivatives that can replace the use of polyoxyetilenamine surfactant in a commercial herbicides. But there is a weakness inthe formula it has low visual appearance to the consumer industry. The aim of this researchwas to study the improvement of herbicide characterization through sonication method. Thisstudy was designed using a complete randomized design of 2 factors with factor 1 is the timeof sonication (0, 30, 60, 90 minutes) and factor 2 is amplitude (20%, 30%, 40%).The bestherbicide formula after sonication at 40% amplitude, 90 minute sonication time having asurface tension of 23,42 dyne/cm, contact angle of 0o and turbidity of 98 NTU.